Estimation of the Beam Width in Magnetic Mass Spectrometer - O.N. Peregudov; E.A. Mironetz (Журнал нано- та електронної фізики)
A method for estimation of the beam width in magnetic sector mass spectrometers is proposed. This method consists in the restoration of the initial ion density distribution function in a beam cross-section before the receiving collector slit and can be used for the qualitative estimation of the mass spectrometer ion-optical scheme.